A rare case of polythelia on the buttock, found incidentally during colonoscopy - Sercombe, Ashleigh M.; Chakraborty , Joy (International Surgery Journal, 2023)
Polythelia or supernummary nipples is a congenital anomaly where more than two nipple- areolar complexes are present. While polythelia is the most common mammary tissue malformation, it is still a rare condition with an incidence of 0.2% to 5.6%. Suppernummary nipples are usually located in the medial embryonic milk lines however, there have been some published cases of atypical locations. We present a case of a 42-year-old male who was incidentally found to have a supernummary nipple on his left buttock on colonoscopy. There was no prior family history of polythelia or any congenital abnormalities.